2020
DOI: 10.1177/0308022620944100
|View full text |Cite
|
Sign up to set email alerts
|

Occupational therapy practice with children with developmental coordination disorder: An online qualitative vignette survey

Abstract: Introduction Children and young people with developmental coordination disorder experience multiple occupational performance and participation challenges across environments. Research to date has not fully explored occupational therapy practice with children with developmental coordination disorder and their families. This study aims to describe current occupational therapy practice with children with developmental coordination disorder. Method This study used a cross-sectional, online qualitative vignette sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Our results indicate that abnormalities in sensory processing, including both discrimination and modulation, should be considered in understanding the possible phenotypes of DCD and developing individualized interventions. Further, given the correlation between sensory modulation scores and social emotional skills, interventions focusing on sensory modulation in DCD (and ASD) may also have the added benefit of improving social skills, mental health, and behavior [ 154 ]. For children with DCD, sensory processing is associated differently with social emotional measures, behavior, and motor skills than for children with ASD and TD children, and further studies are needed to better understand these differences.…”
Section: Discussionmentioning
confidence: 99%
“…Our results indicate that abnormalities in sensory processing, including both discrimination and modulation, should be considered in understanding the possible phenotypes of DCD and developing individualized interventions. Further, given the correlation between sensory modulation scores and social emotional skills, interventions focusing on sensory modulation in DCD (and ASD) may also have the added benefit of improving social skills, mental health, and behavior [ 154 ]. For children with DCD, sensory processing is associated differently with social emotional measures, behavior, and motor skills than for children with ASD and TD children, and further studies are needed to better understand these differences.…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies to date have explored the child’s role in decision-making in this process. Some recent studies have focused on goal-setting practices within pediatric occupational therapy but examined aspects such as therapists perspectives [ 27 , 28 ] and the process of determining goals [ 29 ] without examining decision-making from a child’s perspective. Furthermore, in their scoping review of goal-setting research, Pritchard-Wiart and Phelan [ 24 ] identified that no qualitative studies to date have been conducted with children in pediatric occupational therapy, suggesting the need to examine the child’s perspectives of the goal-setting process.…”
Section: Introductionmentioning
confidence: 99%